2013
DOI: 10.1177/0363546513485406
|View full text |Cite
|
Sign up to set email alerts
|

Bupivacaine Induces Short-Term Alterations and Impairment in Rat Tendons

Abstract: Local anesthetics cause short-term alterations in rat tendons, which, if occurring in humans to a similar extent, may be relevant regarding decreased biomechanical properties and increased vulnerability to tendon overload or injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 40 publications
(49 reference statements)
1
33
0
Order By: Relevance
“…The same accounts for the use of anaesthetics as a control group, which was used in three studies (two in combination with corticosteroids). From a recent animal study, it is known that bupivacaine has detrimental effects on tendon cell viability, which may put the tendon at increased risk of overload or acute injury 31. This stresses the need for placebo-controlled studies in the field of treatments for tendinopathies 32.…”
Section: Discussionmentioning
confidence: 99%
“…The same accounts for the use of anaesthetics as a control group, which was used in three studies (two in combination with corticosteroids). From a recent animal study, it is known that bupivacaine has detrimental effects on tendon cell viability, which may put the tendon at increased risk of overload or acute injury 31. This stresses the need for placebo-controlled studies in the field of treatments for tendinopathies 32.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vitro studies have shown the toxicity of local anesthetics on tendon fibroblasts . Lehner et al reported that the treatment of rat tendon‐derived cells with 0.5% bupivacaine for 10 min had detrimental effects on cell viability . Piper et al showed a toxic effect of 30 min of 1% lidocaine treatment on bovine tendon fibroblasts .…”
mentioning
confidence: 99%
“…Despite the deleterious effects of the local anesthetics as evaluated by in vitro studies, lidocaine is frequently used preoperatively in clinical practice in rotator cuff tears; however, in vivo data on the effects of lidocaine are lacking. These results prompted us to examine how lidocaine acts on rotator cuff tears when used in subacromial injection for this disease.…”
mentioning
confidence: 99%
“…However, both have come under recent criticism and are suggested to generate worse long-term clinical outcomes than conservative treatment alone. Lehner et al (2013) reported on the detrimental effects of bupivicaine on tendon tissue in animal studies, demonstrating that bupivicaine injection increased the tendon vulnerability to injury and overload stress [27]. The use of corticosteroid injections to treat various tendinopathies, while still commonplace in clinical practice, has been repeatedly challenged by authors [28].…”
Section: Control Groupsmentioning
confidence: 99%